Evaluation of Air Pollution in Terms of Sustainability: The Case (Example) of Izmir Carbon Footprint - Çolakoğlu, Ülker; Işik, Ceyda; Aydın, Armağan (Journal of Tourism Sustainability, 2025)
Air pollution is a global problem and significantly impacts every country. Therefore, this study aims to assess the future state of air pollution in Izmir. One of the key innovations of our study is demonstrating how PM (particulate matter) levels specifically influence tourists' destination choices. This study utilizes quantitative data analysis and preprocessing using the Pandas and NumPy libraries. The research methodology is based on data collected from the National Air Quality Monitoring Network. We evaluated the number of ships arriving at Izmir's port from 2008 to 2024 and created maps to visualize changes, including those during the COVID-19 period. Based on our findings, it can be concluded that annual CO (carbon monoxide) and NOX (nitrogen oxide) levels in Izmir are high and are significantly higher in industrial areas than in rural areas. The scenario analysis conducted in this research indicates that if air pollution continues to increase by 15%, air travel will be more severely affected than sea travel. Implementing effective waste management strategies in port cities is believed to benefit both the environment and public health. Practical implications: Key actions to combat air pollution include encouraging local travel habits, increasing the appeal of green transportation options, and raising environmental awareness. Green travel supports a more sustainable transportation system by reducing residents' environmental impact. In the future, informing travelers about ecological damage could lead to changes in travel behavior.